Investigation of the crystal formation from calcium silicate in human dentinal tubules and the effect of phosphate buffer saline concentration - Mi-Jeong Jeon; Jin-Soo Ahn; Jeong-Kil Park; Deog-Gyu Seo (Elsevier, 2024)
Background/purpose: Based on hydrodynamic theory, blocking the dentinal tubules can reduce discomfort caused by dentin hypersensitivity. This study identified the crystals formed in dentinal tubules from tricalcium silicate (TCS) in phosphate-buffered saline (PBS) and evaluated the effect of PBS concentration on crystal formation. Materials and methods: Sixty-nine specimens were made by isolating the cervical part of extracted premolars. TCS was applied by brushing for 10,000 strokes on dentin surface simulating sensitive dentin. Specimens were stored in PBS or solutions with concentrations 1/100, 1/10, 10, and 100 times that of PBS for 1, 30, 60, or 90 days (n = 3). Another nine specimens applied TCS, were immersed in PBS for 3 months, and divided into three subgroups: no treatment, sonication for 10 min, and 1M acetic acid treatment for 3 min. Crystal formation was examined using a scanning electron microscope, assigned five grade scores (0-4) according to maturation, and analyzed by a nonparametric two-way ANOVA (α = 0.05). Crystal components were analyzed using X-ray diffraction (XRD) and energy dispersion X-ray spectroscopy (EDS). Results: The maturation of intratubular crystals was dependent on time and PBS concentration (P < 0.05). In all periods, the high-concentration group showed a higher maturation grade than the low-concentration group. Intratubular crystals were similar to hydroxyapatite according to XRD and EDS, and they withstood sonication and acid application. Conclusion: TCS with nanosized particles formed hydroxyapatite-like crystals in the dentinal tubules, which were dependent on time and concentration of PBS and withstood sonication and acid application.